Comparative transcriptomics in alternate bearing cultivar Dashehari reveals the genetic model of flowering in mango - Kaur, Harmanpreet; Sidhu, Gurupkar Singh; Mittal, Amandeep; Yadav, Inderjit Singh; Mittal, Meenakshi; Singla, Deepak; Singh, Navprem; Chhuneja, Parveen (Frontiers in Genetics, 2023)
Flowering is a complex developmental process with physiological and morphological phases influenced by variety of external and internal factors. Interestingly, many mango cultivars have a high tendency of biennial bearing because of irregular flowering, and has a negative impact on mango flowering and subsequently the yield, resulting in significant economic losses. In this manuscript, transcriptome analysis was carried out on four tissues of mango cv. Dashehari (Bearing tree leaf, shoot apex, inflorescence, and non-bearing tree Leaf). De novo transcriptome assembly of RNA-seq reads of Dashehari with trinity pipeline led to a generation of 67,915 transcripts, falling into 25,776 genes. 85 flowering genes represented by 179 transcripts were differentially expressed in bearing vs non-bearing leaf tissue. Gene set enrichment analysis of flowering genes identified significant up-regulation of flowering-related genes in inflorescence compared to bearing leaf. Flowering genes FT, CO, GI, ELF 4, FLD, FCA, AP1, LHY, and SCO1 were up regulated in the bearing leaf. Pathway analysis of DEGs found significant up-regulation of phenylpropanoid and sucrose & starch pathways in non-bearing leaf compared to bearing leaf. Comparative transcriptome analysis in mango here significantly increases the understanding of the molecular mechanisms driving the flowering process and understanding of alternative bearing in Mango.